Correlation between thoracic photographs and molecular rapid test (TCM) results of tuberculosis patients at the Lasinrang Pinrang Regional General Hospital - Yusa, Andi Hendra; Nasrum, Syifa Nurul Fatimah (Institute Of Computer Science (IOCS), 2025)
Background: Tuberculosis is one of the deadliest infectious diseases in the world, Indonesia ranks third in the world with 824 thousand cases per year. Symptoms of Tuberculosis require a thoracic photograph-like examination with a molecular rapid test (TCM) examination. Although thoracic photographs are effective, they cannot detect infections in other organs, while TCM can diagnose more quickly at a higher cost. Objective: To determine the correlation between thoracic photographs and the results of the Molecular Rapid Test (TCM) of tuberculosis patients at the Lasinrang Pinrang Regional General Hospital. Research Methods: This study uses an observational analytical method with a cross sectional approach. The data used is secondary data, namely the patient's medical records. Research Results: Of the 100 patients studied at Lasinrang Pinrang Hospital, it was found that 80% showed infiltrate lesions on thoracic photographs, followed by 12% with consolidated lesions and 8% with fibrosis lesions. Molecular rapid test (TCM) results showed that 86% of patients were detected positive for Mycobacterium tuberculosis and sensitive to rifampicin, while 14% of TCM results were negative. Conclusion: The study showed that there was a significant relationship between the results of thoracic photo examination in the form of infiltrate lesions, consolidation, fibrosis and calcification to positive and negative results of molecular rapid test (TCM).